Cultivation Optimization and Structural Characterization of Stephanocyclus meneghinianus for Sustainable High-Quality Biosilica Production - Daeryul Kwon; Yoseph Seo; Chaehong Park; Sang Deuk Lee; Taek Lee (Nanomaterials)
This study investigates the potential use of the freshwater centric diatom Stephanocyclus meneghinianus as a sustainable source of high-purity biosilica. We analyzed its morphology, microstructure, and optimal culture conditions, and developed a pretreatment method to recover intact biosilica frustules. The isolated diatoms exhibited small and uniform cell sizes (8–10 μm) with distinctive features such as regularly arranged spines, striae, and fultoportulae. Electron microscopy revealed around 4000 nanoscale pores per valve, mostly along the costae. The pretreatment process using ethanol and hydrogen peroxide effectively removed organic materials and mucilage, preserving the structural integrity of the biosilica. Crystallinity analysis confirmed the amorphous nature of the biosilica, indicating good biodegradability, while elemental analysis showed its composition as being primarily of silicon and oxygen. Growth optimization experiments revealed the highest specific growth rate in DM medium at 20–25 °C under light intensities of 60–120 μmol m−2 s−1. These results demonstrate that S. meneghinianus can be cultured efficiently to produce biodegradable biosilica with well-defined nanostructures. This biosilica shows promise for applications in biomaterials, nanotechnology, pharmaceuticals, and environmental remediation.